PENDEKATAN INTERKONEKSI DALAM STUDI HADIS; (STUDI PEMIKIRAN SYAMSUL ANWAR) - Suwarno, Rahmadi Wibowo (AL-MISBAH (Jurnal Islamic Studies), 2017)
This paper explains Syamsul Anwar's idea of ??the interpretive model of hadith through the interconnection approach. The interconnection model of hadith and astrononomy studies developed by Syamsul Anwar is a novelty in the reconstruction of a new way of reading and understanding in the area of ??study of Hadith studies. The analysis is done by combining the theories of classical, modern (western) hadith and the theory of astronomy (visibility of hilal) simultaneously and synergistically. Referring to the classification of Abdullah Saeed's model of thinking, the interpretation of Hadith's perspective includes the Muslim thinker in the progressive ijtihadist group. That is, traditional Islamic law requires change and reform in order to adapt to the current conditions of society, to support the need for a fressive ijtihad, to combine classical Islamic scholarly thinking with modern Western thought, to believe that social, intellectual, legal, economic and technological change must be reflected in Islamic law.